Economic reasons of chinese merger and acquisition in germany: a takeover between Midea Group and KUKA AG - Liu, Liqin (2020)
Fil: Liu, Liquin. University of Applied Sciences Hochschule Kaiserslautern. Faculty of Business Administration; Alemania.